The effectiveness of soursop leaves extract antibacterial (annona muricata l.) on growth of aureus stafilococus bacteria in oral cavity in-vitro - Ahyar Riza; Miftah A. Kurniadi (Journal of Dentomaxillofacial Science, 2021)
Objective: The aims of the research on soursop leaves extract is to determine antibacterial activity in the extract and which concentration of soursop leaves extract has the greatest antibacterial effect on growth of the oral cavity Staphylococcal Aureus bacterial growth in vitro. Material and Methods: The type of research is an experimental laboratory with a post test only design approach, where this research uses the serial dilusion method with samples of Stafilococcus Aureus bacteria, and uses soursop leaves extract with concentration 90%, 60%, 30%, 10%, chlorheksidin 0,2% control (+) and aquades solution control (-) . This research was carried out by the dilution method and planted on MHA media, then incubated for 24 hours and calculated using colony counter. The results of this research were analyzed by using the One way Annova statistical union. Results: Where the extract concentration of 90% has the highest antibacterial concentration, that is with average 63,00 with the standard division 6,218 and the control - has the lowest anti-bacterial effectiveness 152,25 with a standard deviation of 27,109 . Conclusion: The conclusion of this research is that soursop leaves extract has antibacterial effectiveness against Stafilococcus Aureus bacteria, as the higher the contrantation extract of sour soup leaves as the better antibacterial efectivity through SA bacterium.